Phase equilibrium characteristics of natural gas hydrate formation at the deep-water environment of “Haima” cold seep - Yanyan Huang; Jing-Chun Feng; Yan Xie; Yi Wang; Pian Li; Mingrui Zhang (Energy Reports, 2022)
Methane seeping induced by natural gas hydrate dissociation is ubiquitous in deep-sea environment, which influences the global methane and carbon budget. Nevertheless, the phase equilibrium characteristics that control the stability of hydrate formation during the bubble ebullition process in the in-situ multi-component environment remain unclear. “Haima” cold seep is a typical active methane seeping environment associated with abundant methane hydrate, which necessitates unveiling the potential and stability of methane hydrate formation. This work investigated the hydrate phase equilibrium conditions based on the in-situ water depth with practical ion categories and concentrations for the first time. Results show that Sr2+is an important ion that governs the thermal stability of methane hydrate. Mechanism of different ions categories (Ca2+, Mg2+, and Sr2+) effect on hydrate equilibria can be elucidated by the difference of charge and radius of the ion. Slightly difference of in-situ ion concentrations within the same salinity exerts on unobvious effect on hydrate formation. Moreover, the hydrate stability with H2S-bearing environment coupled with the anaerobic oxidation of methane in the deep-sea floor was enhanced compared to the CO2-bearing environment associated with aerobic oxidation of methane. Furthermore, thermal dynamic conditions of hydrate formation were less rigorous than that in the single methane environment. The response law of hydrate phase transition enthalpy was almost consistent with the phase equilibrium change. This work can give important fundamentals for the estimation of hydrate resources in the practical environment, and have insights for methane capture and fixation in the methane seeps.